An Analysis of Speech Acts in Tourism Services at Toba Lake (Jurnal Bahasa, 2025)
The Indonesian government designates Toba Lake as one of the national tourism destinations with super priority status, referring to areas that receive focused attention in tourism development programmes. In line with this status, improving the quality of tourism services is a crucial aspect, including the use of speech acts by service providers. This study aims to analyse speech acts within the language register of tourism services in the Toba Lake area by applying Searle’s (1969) speech act theory. The study data were obtained from communicative interactions across three tourism service sectors: accommodation, souvenir sales, and restaurants. The findings indicate that the accommodation sector features three categories of speech acts-directive, assertive, and expressive-with four functions of speech acts identified. The souvenir retail sector exhibits four categories of speech acts, namely directive, assertive, expressive, and commissive with six functions identified. The restaurant sector also displays the same four categories of speech acts, although eight functions were identified. All these functions are essential for enhancing the effectiveness of service delivery and improving tourists’ experiences in Toba Lake.Keywords: Speech acts, language register, pragmatics, tourism services, Toba Lake, tourism communication.Full text: PDF